Evaluation of native stingless bee species (Heterotrigona itama and Geniotrigona thoracica) for pollination efficiency on Melon Manis Terengganu - Wahizatul Afzan Azmi,; Wan Zaliha Wan Sembok,; Siti Noraishah Mohd Nasaruddin,; Nur Syazana Azli,; Muhammad Firdaus Mohd Hatta,; Tengku Norulhuda Tg Muhammad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Melon Manis Terengganu (MMT) is a newly developed melon cultivar that is exclusively planted in Terengganu and has monoecious flowers where female and male parts are in different flowers of the same plant. Current practise for MMT pollination mainly depends on humans by hand-cross pollination treatment. However, until now little study on the potential of stingless bees as pollinator for greenhouse MMT has been documented in Malaysia. In this study, two species of stingless bees, Heterotrigona itama and Geniotrigona thoracica were placed with the MMT in the greenhouse. This study is aimed to investigate and compare the quality of MMT produced by four different pollination treatments; (1) self-pollination, (2) hand-cross pollination, (3) H. itama pollination and (4) G. thoracica pollination. Two hives of each stingless bee species were placed into the greenhouse at least two days before the MMT flowers bloomed. MMT produced from pollination by both stingless bee species and hand-cross pollination were significantly heavier in fresh weight, larger in diameter, higher in total soluble solid (TSS), and greater number of seeds per fruit compared to those produced from self-pollination. Pollination by stingless bees reached fruits with higher sweetness than hand-cross pollination and self-pollination. Results revealed that the stingless bee pollination on MMT production was similar to the MMT produced from hand-cross pollination. This study provides essential information on the potential of native stingless bees, H.itama and G. thoracica which can be effective pollinators for the MMT grown in the greenhouse besides manual pollination.